Evaluasi Kinerja Operasional dan Pelayanan Trans Jateng Koridor VII Solo - Wonogiri - Nabila, Em Faiqsa David; Putro, Hanendyo; Fitriani, Nurul (Universitas Batanghari Jambi, 2025)
Trans Jateng Corridor VII Solo–Wonogiri is a public transportation service that plays an important role in supporting the mobility of the community in the Surakarta area and its surroundings, although it still faces challenges in terms of operational efficiency and user satisfaction. This study aims to evaluate the operational and service performance of the corridor and to develop recommendations for improving service quality. The study was conducted in accordance with the Director General of Transportation Regulation No. 687 of 2002 and the Ministry of Transportation Regulation No. 10 of 2012, with data collection through dynamic surveys, static surveys, and user satisfaction questionnaires. Service performance analysis used the Customer Satisfaction Index (CSI) method to obtain a comprehensive overview of customer satisfaction. The research results indicate that most operational indicators have met the established standards, although some indicators such as load factor, number of passengers, and headway are still below the ideal target. The user satisfaction level based on the CSI method reached 76.85% and falls into the satisfied category; however, several service aspects such as seatbelts, bus capacity, standing area size, and service information still need improvement. Therefore, strategic recommendations have been formulated, focusing on improving operational efficiency and service quality to meet public expectations and enhance the comfort of Trans Jateng users.